Analisis Kelayakan Usaha Selada Kebun K24 Hidroponik di Desa Bojongsari, Kecamatan Alian, Kabupaten Kebumen - Jumadi Jumadi; Nurlaila Fatmawati (Jurnal Kridatama Sains dan Teknologi, 2026)
Lettuce is a vegetable with a broad market and high economic value, making it a promising candidate for hydroponic cultivation. This study aimed to assess the financial and non-financial feasibility of hydroponic lettuce production at the K24 Hydroponic Farm. The non-financial analysis covered legal, marketing, technical, human resource management, and socio-environmental aspects, while the financial analysis examined revenue, the R/C ratio, and the Break-Even Point (BEP). The research location was selected purposively because it is an active hydroponic farming operation. Purposive sampling was employed to select the respondent: the manager of the K24 Hydroponic Farm. The results indicate that the K24 Hydroponic Farm business is feasible from both financial and non-financial perspectives, except for legal and human resource management aspects. Financial analysis revealed an average annual revenue of IDR 217,828,002.00, an R/C ratio of 7.37, a BEP in volume of 1,366.88 kg, and a BEP in price of IDR 3,390.08/kg. Consequently, the K24 Hydroponic Farm business is deemed feasible to operate.